The socio-ecology of child institutionalisation and foster care in Souss Massa, Morocco: a qualitative study - Fadi Baghdadi; Christopher Hands; Ann John; Ashrafunnesa Khanom; Mary Elizabeth Rauktis; Abdellah Soussi; Helen Snooks (Child Protection and Practice)
Background: The high number of children living in institutions in Morocco is driven by complex socio-economic, cultural, and historical factors, with limited alternative care and research to inform interventions. Objective: To understand the socio-ecological factors contributing to child institutionalisation and explore the potential for foster care as an alternative in the Souss Massa region of Morocco. Participants: Nine boys and eight girls living in two institutions, and 10 fathers and 17 mothers of children at risk of entering institutions in the Souss Massa region of Morocco. Methods: A total of five focus groups with children and parents to explore the causes and consequences of institutionalisation and perceptions of foster care. Children created issue trees to facilitate focus group discussion. Data were coded and interpreted by a team of three researchers using the socio-ecological model for analysis and to understand the interplay between family dynamics, economic conditions, societal norms, and cultural beliefs on child institutionalisation. Findings: Key drivers of institutionalisation included poverty, neglect, hostile home environments, family breakdown, and societal stigma. Despite some hesitancy, by children and parents, the concept of foster care emerged as a viable alternative. Conclusions: This study highlights the need for interventions at multiple ecological levels, including low-cost improvements to institutional care and transitional support, alongside broader legal reforms, the strengthening of social services, and community-based programmes. Foster care has potential as an alternative, but its success will depend on legislation and active community engagement.